Impact of Age, Sex, and Renal Function on the Efficacy and Safety of Direct Oral Anticoagulants vs. Vitamin K Antagonists for the Treatment of Acute Venous Thromboembolism: A Meta-Analysis of 22,040 Patients - Zhou, Bo; Wu, Haoyu; Wang, Chen; Lou, Bowen; She, Jianqing (Frontiers in Cardiovascular Medicine, 2021)
Objective: In the present study, we conducted a meta-analysis to assess the impact of age, sex and renal function on the efficacy and safety of direct oral anticoagulants (DOACs) vs. Vitamin K antagonists (VKAs) for the treatment of acute venous thromboembolism (VTE). Methods: Electronic databases (accessed till June 2021) were systematically searched to investigate RCTs evaluating apixaban, dabigatran, edoxaban, and rivaroxaban versus VKAs for the treatment of acute venous thromboembolism. Results were presented as odds ratio (OR) and 95% confidence intervals (CI). Results: DOACs was associated with a borderline higher efficacy in female (OR 0.79, 95% CI 0.62–1.02), and a significantly higher efficacy in patients with age more than 75 (OR 0.51, 95% CI 0.32–0.80) and creatinine clearance less than 50 mL/min (OR 0.57, 95% CI 0.32–0.99). The primary safety endpoint of major or clinically relevant non-major bleeding was significantly reduced in DOACs as compared to VKAs in patients both less than 75 (OR 0.79, 95% CI 0.70–0.89) and more than 75 (OR 0.75, 95% CI 0.59–0.96). DOACs also show advantage in terms of major or clinically relevant non-major bleeding in male (OR 0.72, 95% CI 0.60–0.86), and patients with creatinine clearance more than 50 mL/min (OR 0.75, 95% CI 0.67–0.84). Conclusions: DOACs have exhibited clinical preference among acute VTE patients with decreased thrombosis and bleeding events, especially in patients with age more than 75 and creatinine clearance less than 50 mL/min.